Transient stability enhancement control through VSC-HVDC system and fast frequency response resources - Xu, Qingshen; Lou, Jie; Ning, Dalei; Li, Peihao (Frontiers in Energy Research, 2023)
Besides the traditional long-distance, bulk power transmission application, the HVDC system can bring additional benefits to the system by providing ancillary service. HVDC system can regulate its power flow in a very short time that could be used to provide emergency support to rescue the disturbed system from the very bad condition. However, because traditional generators cannot meet the great power demand of the HVDC system in a short time, the fast response of the HVDC system may cause severe power-unbalance events in the power supporting system. In this paper, a combination frequency response control is proposed for the fast frequency response and HVDC system coordinating under the contingency. With the proposed combination frequency response control, the frequency response capacity of the HVDC system could be made the most use. Meantime, the coordination between the HVDC system and fast frequency response (FFRs) could also avoid the frequency of the power-source-provided system dropping into an unacceptable level. The simulation study is conducted on a highly reduced power system model of the three North American interconnections. The simulation verification shows the effectiveness and feasibility of the proposed combination frequency response control and indicates that the frequency stability for both side system of the HVDC system could be significantly improved with the proposed combination frequency response control.